2022
DOI: 10.3390/foods11111645
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Quality Analysis of Radio Frequency-Hot Air Combined Segmented Drying of Wolfberry (Lycium barbarum)

Abstract: To overcome the problems of a long conventional drying time, low energy efficiency, and poor product quality, a segmented drying approach was developed for fresh wolfberry (Lycium barbarum) using a radio frequency (RF)-hot air drying process, which was investigated under different parameters of plate spacing (80, 90, 100 mm), vacuum degree (0.015, 0.025, 0.035 Mpa), and hot air temperature (50, 55, 60 °C). Analysis of the wolfberry’s drying characteristics, comprehensive quality, and microstructure indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The polysaccharide content was 179.92 mg/g at the drying temperature of 50 °C, which increased by 42.84% compared with that at 35 °C (125.96 mg/g). This may be due to the low drying temperature, which increased the time for the Maillard reaction and caramelization reaction between amino acids and polysaccharides, and therefore the polysaccharide content decreased [ 37 , 39 ]. It is also known that the polysaccharide contents of the samples were 140.96 mg/g and 141.80 mg/g at section thicknesses of 3 mm and 4 mm, which were higher than the polysaccharide contents at other thicknesses, indicating that the samples could retain the bioactive substances better under this condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polysaccharide content was 179.92 mg/g at the drying temperature of 50 °C, which increased by 42.84% compared with that at 35 °C (125.96 mg/g). This may be due to the low drying temperature, which increased the time for the Maillard reaction and caramelization reaction between amino acids and polysaccharides, and therefore the polysaccharide content decreased [ 37 , 39 ]. It is also known that the polysaccharide contents of the samples were 140.96 mg/g and 141.80 mg/g at section thicknesses of 3 mm and 4 mm, which were higher than the polysaccharide contents at other thicknesses, indicating that the samples could retain the bioactive substances better under this condition.…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharide was determined by the sulfuric acid-phenol method [ 39 ]. A 0.005 mL extract was taken, 1.0 mL 9% phenol solution was added, fully mixed, added 3.0 mL concentrated H 2 SO 4 , shaken for 5 min, room temperature reaction for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the convert moisture content decreased from 40 g•g −1 to 20 g•g −1 , the drying time of microwave vacuum increased from 8 to 19.3 h, while the total drying time of reaching the storage moisture content decreased from 71 to 37.6 h. It could be seen that the use of segmented drying shortened the drying time. Xu et al (2022) studied drying characteristics of wolfberry by using segmented drying of radio frequency combined with hot air, Li et al (2020) studied drying characteristics of Huyou fruit by using segmented drying of microwave vacuum combined with freeze, indicating that segmented drying can shorten the drying time of drying method with long drying time (e.g., hot air and freezing) and achieve high quality dehydration. Due to microwave vacuum heated the sample from inside to outside, the heat transfer direction of the sample was the same, and the vacuum environment was conducive to the transfer of water.…”
Section: Results and Analysismentioning
confidence: 99%
“…Color is one of the important indexes to evaluate the quality of agricultural products. Xu et al (2022) found that compared with hot-air drying and radio-frequency drying, pretreatment shortened the total drying time, increased the drying rate, and reduced the Maillard reaction time (Çakmak et al, 2016;Jiang et al, 2022). To a certain extent, it inhibited the oxidative decomposition of natural active substances and the degradation of thermosensitive nutrients.…”
Section: 21mentioning
confidence: 99%